Promoting healthy sexual practices to prevent youth pregnancy in Vhembe district - Khosa, Ntiyiso Vinny; Mudau, Azwinndini Gladys; Makhado, Lufuno (Curationis (Pretoria), 2025)
Background Termination of pregnancy has a negative health impact on the lives of youth. Myth and illegal consultation on the termination of pregnancy from unprofessional healthcare personnel, which results in negative consequences on the health and future of youth. Objectives The purpose of this study was to examine healthy sexual practices to lessen the termination of unplanned pregnancies among youth in the Vhembe district. Method A quantitative survey method was used in this study. A stratified random sampling was used to select sample size of 531 participants. Self-structured questionnaires and the SurveyMonkey were used to collect data. Pre-test was used to check the reliability of the instrument in the study. Data were analysed using Stata version 18. The approval to conduct the study was received from the University of Venda and the Department of Basic Education. Results The findings showed that 56% of the participants agreed that the average waiting period at the public health facility is exceedingly long for pregnancy termination. 53.9% of the participants agreed that language used to give instructions by healthcare regarding the termination of pregnancy is a barrier. 48.8% of the participants agreed that the lack of pregnancy termination resources deterred youth from visiting health facilities. Conclusion Promoting healthy sexual practices among youth is vital in lessening the termination of unplanned pregnancies. Education on contraception use, abstinence and open communication between partners can help young people make informed decisions about their sexual health and prevent unintended consequences. Contribution The study illustrates a good piece of innovative work in health promotion in disadvantaged communities in Vhembe district.